Trade in tasks: Revisiting the wage and employment effects of offshoring - Wilhelm Kohler; Jens Wrona (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
We revisit Grossman and Rossi-Hansberg's (2008) famous result, that under certain conditions offshoring of low-skilled labor tasks raises the domestic wage for low-skilled workers. Our re-examination features a less benign environment where Rybczynski-type reallocation of factors to absorb offshoring-induced job displacement is ruled out. We allow for simultaneous offshoring of both skilled and unskilled labor, and we derive new results on the role of factor-bias in offshoring, identifying conditions under which offshoring has a "lifiting-all-boats" effect benefitting all workers. Extending our analysis to a frictional labor market with equilibrium unemployment due to costly matching, we demonstrate that under these same conditions offshoring is also associated with rising employment.
Keywords: F11; F16; J64; 330; Offshoring; Trade in Tasks; Wages; Unemployment; Search and Matching